2013
DOI: 10.1007/s10930-013-9523-0
|View full text |Cite
|
Sign up to set email alerts
|

Phenoloxidase Activity of Helix aspersa Maxima (Garden Snail, Gastropod) Hemocyanin

Abstract: The oxygen-transporting protein, hemocyanin (Hc), of the garden snail Helix aspersa maxima (HaH) was isolated and kinetically characterized. Kinetic parameters of the reaction of catalytic oxidation of catechol to quinone, catalyzed by native HaH were determined: the V max value amounted to 22 nmol min(-1) mg(-1), k cat to 1.1 min(-1). Data were compared to those reported for other molluscan Hcs and phenoloxidases (POs). The o-diphenoloxidase activity of the native HaH is about five times higher than the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The function HMC in invertebrate is not only as a respiratory protein via oxygen transport, but it has also been strongly associated with different immunological processes [6066]. HMC has been shown to participate in multiple roles of the immune response including phenoloxidase activity [6164], antiviral [65] and antimicrobial activity [66]. In snails, a study on the transcriptional profile of B .…”
Section: Discussionmentioning
confidence: 99%
“…The function HMC in invertebrate is not only as a respiratory protein via oxygen transport, but it has also been strongly associated with different immunological processes [6066]. HMC has been shown to participate in multiple roles of the immune response including phenoloxidase activity [6164], antiviral [65] and antimicrobial activity [66]. In snails, a study on the transcriptional profile of B .…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosinase plays a crucial role in melanin biosynthesis pathway that is responsible for melanogenesis of animals [3]. And it actually catalyzes the hydroxylation of tyrosine to L-DOPA (L-3, 4-dihydroxyphenylalanine) and the subsequent oxidation of L-DOPA to DOPA quinone [4,5] which transforms into melanin and other polyphenolic compounds after a series of spontaneous chemical reactions [6]. Overproduction of melanin may lead to a variety of skin diseases, such as melasma, age spots and freckles [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have reported different versions of tyrosinase-based biosensors for detection of phenols in environmental samples [33][34][35][36]. Two recent reports, one from our group [7] and the other by Raynova et al [5] described hemocyanin-based optical biosensors built by immobilizing molluscan hemocyanin on a thin film of chitosan coated on a glass slide. This first-generation sensor was able to detect catechol at concentrations of 5 ppm to 90 ppm.…”
Section: Discussionmentioning
confidence: 99%
“…However, it suffers from lower affinity for bulky phenolic substrates. Currently, optimal phenoloxidase activity in hemocyanins is obtained by either carrying out limited proteolysis [5] or pretreatment with SDS [7], prior to its immobilization on sensors. Thus, it is important to understand the structural changes caused by the action of proteolytic agents or SDS resulting in an increase in the affinity of the protein for bulky phenolic substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation